Acupuncture and moxibustion stimulate fibroblast proliferation and neoangiogenesis during tissue repair of experimental excisional injuries in adult female Wistar rats. Issue 2 (April 2020) - Alonso, Hamilton Ricardo; Kuroda, Fabricio Campos; Passarini Junior, José Roberto; Quispe Cabanillas, Juan Guzman; Mendonça, Fernanda Aparecida Sampaio; dos Santos, Glaucia Maria Tech; de Aro, Andrea Aparecida; do Amaral, Maria Esméria Corezola; Marretto Esquisatto, Marcelo Augusto
Objective: To investigate the effects of acupuncture and moxibustion on the repair of excisional skin injuries on the back of adult female Wistar rats. Methods: 90 animals were divided into three groups: C, control; A, acupuncture treatment (needled at traditional acupuncture points BL13, BL17 and ST36); M, moxibustion treatment (overlying same traditional acupuncture points). They were euthanased on days 7, 14 and 21 after injury for removal and preparation of tissue for analysis. Results: The treated groups (A and M) showed no changes regarding the structural analysis relative to the control (C) group. The total number of fibroblast cells in the A and M groups were significantly higher than those in the C group on days 14 and 21. The number of granulocytes was significantly less in the A and M groups compared with the C group on days 14 and 21. The total number of newly formed vessels increased on day 21 and was significantly higher in the A and M groups. The amount of birefringent collagen fibre detected on day 21 was significantly higher in the C group. The amount of glycosaminoglycan and hydroxyproline was similar between the groups. The amount of collagen I did not differ between the groups in any period, despite the increased amount detected over time. The amount of type III collagen did not differ between the groups but the detected amount decreased over the course of the experiment. The amount of transforming growth factor β1 (TGF-β1) and vascular endothelial growth factor (VEGF) in the A and M rats was similar but inferior to C rats across all experimental periods. Conclusions: Acupuncture and moxibustion stimulated fibroblast proliferation and neoangiogenesis, and extended the period of collagen fibre reorganisation in the repair of excisional injuries in adult female rats.